Glucose Challenge Test and Association with Pregnancy Outcome - Özkaya, Enis; Karadağ, Burak; Yerebasmaz, Neslihan; Aldemir, Oya; Düzgüner, Soner; Çakır, Evrim; Erkaya, Salim (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: We designed this study to evaluate the relationship between glucose intolerance and pregnancy outcome in terms of birth weight and cesarean (C/S) rates. STUDY DESIGN: Two hundred fifty eight pregnancies were included in the study. After delivery birth weights and route of deliveries were recorded and oral glucose challenge tests with 50 grams were viewed from records. RESULTS: Mean age, gravida, parity, glucose challenge test (GCT), birth and maternal weights were 25.6±5.3, 1.9±1.5, 0.6±0.9, 105.9±26.9 mg/dl, 3235±469 gr, 75.04±12 kg respectively. Correlation analysis revealed a significant positive correlation between GCT result with maternal age, gravida and maternal weight (95% CI, r=0.334, p:0.001, r=0.300, p:0.001, r=0.201, p:0.003 respectively). A significant negative correlation with birth weight was found. (r=-0.167,p=0.007). GCT level between 120-140 mg/dl was found to be significantly associated with low birth weight (LBW) and values of 120-160 mg/dl were positive confounder for higher C/S rates. CONCLUSION: In this study GCT results between 120-140 mg/dl were found to be risk factor for LBW after adjustment of other confounders and this value and higher values up to 160 mg/dl were positive confounders for C/S rates.